THE CONCEPT OF "BIRDS" IN THE PHRASEOLOGICAL LANDSCAPE (BASED ON ENGLISH MATERIALS) - Usenova Gulmira Abillayevna; Rustamova Melhriniso Rashid qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation This article explores the concept of "birds" in English phraseology, analyzing how avian imagery is embedded in idioms, proverbs, and fixed expressions. Birds serve as powerful symbols in language, reflecting human emotions, behaviors, and cultural beliefs. The study categorizes bird-related phrases, examines their semantic functions, and discusses their metaphorical meanings. By reviewing linguistic and cultural sources, the article highlights the universality and diversity of bird symbolism in English.